Mysteries of science fiction: postcritique, cognition, and genre - Bartolotta, S (2023)
At least since Darko Suvin’s pioneering work in the 1970s, science fiction criticism has been vitally shaped by Marxist and critical theory, with a corresponding reliance on the diagnostic methodology of what has been called, in a phrase coined by Paul Ricoeur and adopted by contemporary postcritique, “hermeneutics of suspicion.” This thesis offers the first sustained attempt to establish an analytical framework for a postcritical understanding of science fiction, operating a reconceptualization of Suvin’s theory of cognitive estrangement through insights from postcritique and cognitive literary studies. The concept of affordative estrangement is thus offered as a non-mutually exclusive alternative to Suvin’s model, and presented as a notion capable of unlocking a textual approach that does not rely on the metaphorical or allegorical readings that are traditionally favoured in the study of nonrealist literature. This approach is then implemented through analyses of texts of speculative fiction that display a generic hybridization with the major traditions of crime and mystery literature: spanning from the late-nineteenth to the early twenty-first century, texts examined include British occult detective fiction, Isaac Asimov’s Robot series, Stanisław Lem’s detective novels, and five cybernoir novels. The interest in the form of the SF mystery is motivated by how these texts idiosyncratically unite the cognitive potential of science-fictional estrangement with the structural self-reflexivity of the mystery story, thus foregrounding the aesthetically and cognitively generative qualities of science-fictional discourse that, in the postcritical reading presented in this study, engender the cogency of science fiction once this is displaced from the analytical coordinates of critical theory.